Thematic evolution of research on hospital management: A longitudinal study based on Scopus - García García, Rosa Elgiba (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. The thematic evolution of research in hospital management was examined using bibliometric techniques. Design/Methodology/Approach. The Scopus database was used as the source for extracting literature. The document type and relevant journals were identified. VOSviewer was used to create co-word maps that reflected the thematic evolution during the following periods: 1) 1986-1994, 2) 1995-2004, 3) 2005-2014, and 4) 2015-2024. Results/Discussion. Scientific production showed an annual growth trend, with slight decreases. In the context of the Bradford areas, three groups of journals emerged. The United States and China emerged as leaders in research. About topics by subperiod, we found that during the first decade (1986-1994), the topics addressed focused on cost-benefit analysis, data analysis, information technologies, and hospital information systems. During the second decade (1995-2004), topics related to clinical management and quality of care were addressed. During the third decade (2005-2014), studies on the facilities provided by information technologies and the results of innovation in resource management, as well as improvements in the quality of patient care, prevailed. During the last decade (2015-2024), studies focused mainly on gender analysis and the masculinization of the profession. Artificial intelligence and hospital management, as mediated by the COVID-19 pandemic, marked the fundamental trends of the last decade. Conclusions. Hospital management was structured around various thematic areas that addressed management from the perspective of clinical management and quality of care, pre-hospital management and emergencies, technology and innovation in hospital management, emergency preparedness and response, economic aspects and resource use, ethics and legal aspects, and education and training in hospital management. There was also evidence of a lack of specialization in terms of authorship, institutional affiliation, and journals.